Artificial Intelligence (AI) Architecture for Integrated Smart Digital Banking System - Bambang Sugiharto; Harkim; Rejekia V Simanungkalit; Ilhamsyah Siregar; Maya Andriani (Jurnal Penelitian Pendidikan IPA, 2023)
Using artificial intelligence, physicists have condensed a daunting quantum problem that until recently required 100,000 equations into a task of as few as four equations - all without sacrificing accuracy. Artificial intelligence is becoming the most current achievement of the computing world. The human brain is to some extent represented and spliced with the ability to solve problems. The purpose of this study is to describe in detail how the power of artificial intelligence with its complex system can help the needs of digital technology in the banking sector. The research method used is the elaboration of great thoughts and facts about artificial intelligence. Scientific data is interpreted with analytical power that is as precise as possible, so as to produce a description that meets the logic of structured thinking. The data is taken from relevant and up-to-date literature, the work of scientists who have been disseminated in various weighty scientific publications at the world level. The results of the study found how artificial intelligence has folded the complexity of the problem into a simple solution. Artificial intelligence in the banking world becomes an instrument that integrates consumers, smartphones, databases, security systems, financial services authorities, agencies, law enforcement officers, and various derivative digital systems.